Criminal defence services: users’ perspectives: an interim report - Kemp, Vicky; Balmer, Nigel (Legal Services Research Centre, 2008)
A survey was undertaken of over 1,000 people drawn into the criminal justice system in order to find out more about their choice and use of a solicitor: 212 suspects interviewed in police stations, 767 in magistrates’ courts and 163 female prisoners. It was found that people value having a choice of a solicitor with 9 out of 10 respondents saying this was important. Their choice of a solicitor was based mainly on a recommendation and what was important to people was having a ‘good’ solicitor, someone who is experienced, knowledgeable and knows what they are doing. It was also important to respondents to be able to communicate well with their solicitor. There was some confusion over the independence of the police station duty solicitor with a significant minority of respondents believing this was a lawyer employed directly by the police. Of those who did not have a solicitor in the police station most simply said they ‘did not need’ one while others were concerned this would cause a delay. The survey also highlighted people’s understanding of what was happening in the criminal process with those whose first language was not English being less likely to understand what was happening and also less likely to have a solicitor when compared to those whose first language was English.